A Sociological Study of the Effect of Academic Socialization Process on Knowledge Sharing (Case Study: Postgraduate Students of Shahid Chamran University of Ahvaz) - masoumeh bagheri; ali boudaghi; zahra poureisa (توسعه اجتماعی, 2024)
Today, in the university system, knowledge sharing plays a key role in realizing organizational goals, especially knowledge creation and university entrepreneurship. Knowledge sharing behavior among academic activists is facilitated by effective training and dynamic socialization. The main purpose of the current research is to study the effect of the academic socialization process on knowledge sharing among graduate students of Shahid Chamran University of Ahvaz. The research method is a survey and in order to collect information from the technique the questionnaire was used. The statistical population of the research includes 6114 graduate students of Shahid Chamran University of Ahvaz, from which 362 people were selected using Cochran's formula with a simple random sampling method. The results of the research analysis show: The average of knowledge sharing among graduate students of Shahid Chamran University of Ahvaz is 42.29 and it is moderate to low, also, a significant relationship was observed between the variable of academic socialization and its dimensions with knowledge sharing. The results of the regression analysis showed that the variables of academic encouragement, student-teacher interaction and scientific participation explain 48% of the changes in the dependent variable. By comparing the beta coefficients, it can be said that the dimension of scientific encouragement of academic socialization with a beta coefficient of 0.388 has the greatest effect and the dimension of student-to-student interaction with a beta coefficient of  0.106 has the least effect on knowledge sharing.